Effects of Feeding Oxalic Acid to Pregnant Rats - Abdul Rahman, Sheikh Omar; Schiefer, H. B. (1980)
Two studies were carried out. The aim of the pilot study was to find a suitable dose ofoxalic acid to be used in the principal study. Thirty pregnant Wister rats were used in the p'rincipal study divided into three groups of 10 animals each. The animals in two groups received oxalic acid at 0.035 g and 0.045 g per day per animal until parturition. The animals in the third group received normal saline. No abortions, gross malformations or renal oxalosis were observed in the foetuses and newborn in both studies. However changes comparable to tubulonephrosis were observed in the newborn in the group receiving 0.03 gf day in the pilot study. A correlation was observed in the principal study between the dose of oxalic acid and renal oxalosis in the dams as well as differences in litter size. Possible reasons for these observations were discussed